2019
DOI: 10.1093/ofid/ofz503
|View full text |Cite
|
Sign up to set email alerts
|

ESKAPE Pathogens in Bloodstream Infections Are Associated With Higher Cost and Mortality but Can Be Predicted Using Diagnoses Upon Admission

Abstract: Background ESKAPE bacteria are thought to be especially resistant to antibiotics, and their resistance and prevalence in bloodstream infections are rising. Large studies are needed to better characterize the clinical impact of these bacteria and to develop algorithms that alert clinicians when patients are at high risk of an ESKAPE infection. Methods From a US data set of >1.1 M patient encounters, we evaluated if ESKA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 39 publications
4
39
1
1
Order By: Relevance
“…The diagnosis criteria were determined by the de nitions of National Healthcare Safety Network and CDCP [19]. ESKAPEEc were previously de ned elsewhere [1][2]4,12]. The de nition of MRD was based on the international expert proposal for interim standard [20].…”
Section: De Nitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis criteria were determined by the de nitions of National Healthcare Safety Network and CDCP [19]. ESKAPEEc were previously de ned elsewhere [1][2]4,12]. The de nition of MRD was based on the international expert proposal for interim standard [20].…”
Section: De Nitionsmentioning
confidence: 99%
“…The notorious group of pathogens, Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter spp, named "ESKAPEEc" owing to their high resistances to multiple antimicrobial agents, have recently aroused global concern [1][2].Currently, the incidence of bloodstream infection (BSI) caused by ESKAPEEc has increased rapidly [3], and ESKAPEEc BSI brought about worse outcomes [3], longer hospital stays, higher economic costs [4][5][6], and increased mortality [4][5][6].In addition, effective antimicrobial agents against ESKAPEEc strains were limited due to the growth of resistance to multiple antibiotics in these bacterial species. Inappropriate and delayed empirical antimicrobial agents treatment for patients with BSI was connected with high risk of mortality [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among antibiotic resistant bacteria, "ESKAPE" pathogens, including Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species [4], cause the majority of hospital infections with higher mortality of patients. "ESKAPE" pathogens effectively escape the effects of commonly used antibacterial drugs, and are usually associated with significantly higher economic burden by increasing the duration of hospital stays and deceasing workforce productivity [3,5]. Recently, a notable study reported that ESKAPE pathogens represented 42.2% of species isolated from bloodstream infections in the United States [5].…”
Section: Introductionmentioning
confidence: 99%
“…"ESKAPE" pathogens effectively escape the effects of commonly used antibacterial drugs, and are usually associated with significantly higher economic burden by increasing the duration of hospital stays and deceasing workforce productivity [3,5]. Recently, a notable study reported that ESKAPE pathogens represented 42.2% of species isolated from bloodstream infections in the United States [5]. Moreover, compared with patients infected with non-ESKAPE pathogens, patients presenting ESPAKE-bloodstream infections were associated with a 3.3-day increase in length of hospital stay, and a 2.1% absolute increase in mortality [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation